1985
DOI: 10.1016/s0022-5347(17)49278-0
|View full text |Cite
|
Sign up to set email alerts
|

Histological Changes Occurring in the Contralateral Testes of Prepubertal Rats Subjected to Various Durations of Unilateral Spermatic Cord Torsion

Abstract: Prepubertal rats were exposed to unilateral spermatic cord torsion for 0, 1, 3, 5, 9 or 12 hours duration. At the end of this time the damaged testes were either removed or untwisted and pexed into place. The animals were then allowed to mature to 77 days of age at which time the contralateral testes were examined for 12 histological parameters and scored according to the degree of pathology noted in each. Pathological changes in the contralateral testes were found to be dependent on the duration of spermatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 12 publications
9
103
0
2
Order By: Relevance
“…Unsal et al 16 Good results were also obtained by Avlan et al 17 , whose study involved 720° torsion and ischemic time of 4h, administration of selenium, and histological evaluation based on Cosentino et al 9 .…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…Unsal et al 16 Good results were also obtained by Avlan et al 17 , whose study involved 720° torsion and ischemic time of 4h, administration of selenium, and histological evaluation based on Cosentino et al 9 .…”
Section: Methodsmentioning
confidence: 93%
“…Yurtçu et al 20 performed 720º torsion of spermatic cord for 6h and administered melatonin before detorsion. Histological evaluation, conducted according to Cosentino et al 9 , revealed a good level of protection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The histological parameters was scored according to Cosentino and colleagues's classification (Table 1). 21 …”
Section: Histological Examinationmentioning
confidence: 99%